Morphological Diversity among Accessions of Apple Tree (Malus × Domestica Borkh) - Simon Mada Mbovora; Cousin Musvosvi; Edmore Gasura (Advances in Agriculture, 2021)
Worldwide, apple ranks fourth in terms of economic importance after citrus, grapes, and bananas with a world production of above 71 million tonnes per year. Apple accessions that are in cultivation throughout the world appear to have come from a genetically similar source. Their diversity has further been decreased through the use of preferred few accessions in breeding programmes. Determination of morphological diversity among the accessions maintained at Nyanga Experimental Station is key for identification and informed use of the accessions in adaptive research. The purpose of this study was to determine the extent of morphological diversity among apple accessions conserved at Nyanga Experimental Station, Zimbabwe, and identify promising accessions for use as cultivars in warmer environments. Sixty-eight Malus domestica accessions of worldwide provenance all maintained at Nyanga Experimental Station were evaluated in a complete randomized design with three replications. The experiment was managed following the standard cultural practices for apples. Characterization using morphological markers was done following the format of the International Board for Plant and Genetic Resources (IBPGR). Data were subjected to cluster analysis based on the unweighted paired group method using arithmetic averages (UPGMA) method. A narrow genetic diversity was observed as reflected by the pairwise genetic similarity matrix that ranged from 80 to 100%. Promising accessions such as Anna, Mayaan, Michal, Elah, Tydeman’s Early Worcester, Discovery, and Mollies Delicious were identified for use as cultivars in warmer areas.